2015
DOI: 10.1108/mmms-01-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Elastic moduli of boron nitride, aluminium nitride and gallium nitride nanotubes using second generation reactive empirical bond order potential

Abstract: Purpose -The purpose of this paper is to study elastic properties of III-V nitride nanotubes (NNTs) using second generation (REBO) potential. Design/methodology/approach -In the present research paper elastic properties of BN, AlN and GaN nanotubes have been investigated, using the second generation REBO potential by Brenner and co-workers, which is a bond order potential earlier used for carbon nanostructures successfully. In the present calculation, the same form of potential is used with adjusted parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The greatest differences of about 3.9, 4.5, and 5.8% are observed when E NT evaluated by (Eq. ( 16)) is compared with Young's modulus reported by Kumar et al [44], Li and Chou [48], and Santosh et al [42], respectively. The works of Santosh et al [42] and Kumar et al [44] both used MD simulation, with the difference in the way of describing the interatomic interactions in the h-BN lattice, force-constant method, and REBO potential, respectively.…”
Section: Elastic Moduli Of the Single-walled Boron Nitride Nanotubes ...mentioning
confidence: 88%
See 2 more Smart Citations
“…The greatest differences of about 3.9, 4.5, and 5.8% are observed when E NT evaluated by (Eq. ( 16)) is compared with Young's modulus reported by Kumar et al [44], Li and Chou [48], and Santosh et al [42], respectively. The works of Santosh et al [42] and Kumar et al [44] both used MD simulation, with the difference in the way of describing the interatomic interactions in the h-BN lattice, force-constant method, and REBO potential, respectively.…”
Section: Elastic Moduli Of the Single-walled Boron Nitride Nanotubes ...mentioning
confidence: 88%
“…( 16)) is compared with Young's modulus reported by Kumar et al [44], Li and Chou [48], and Santosh et al [42], respectively. The works of Santosh et al [42] and Kumar et al [44] both used MD simulation, with the difference in the way of describing the interatomic interactions in the h-BN lattice, force-constant method, and REBO potential, respectively. Li and Chou [48] investigated the elastic behaviour of the SWBNNTs within the framework of the NCM/MSM approach with beam elements to model the B-N bond, as in the present study, using only the other force field constants (see, Table 2).…”
Section: Elastic Moduli Of the Single-walled Boron Nitride Nanotubes ...mentioning
confidence: 95%
See 1 more Smart Citation
“…Since the discovery of single-walled carbon nanotubes (SWCNTs) in 1992 [1] , nanotubes have been the subject of considerable interest, due to their one-dimensional microstructure and unique mechanical [2][3][4][5][6][7] , thermal [8][9][10] , electrical [11][12][13][14][15][16][17] , and mass transport properties [18,19] . Over the past two decades, SWCNTs have been implemented in a variety of applications, including sensors [20][21][22] , power generation systems, nanocomposite materials [23,24] , and molecular separation [19,25] .…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the elastic modulus of the BNNT reduces by exerting the external electrical field. Kumar et al [38] compared the elastic modulus of the BNNTs with aluminum nitride nanotubes (AlNNTs) and gallium nitride nanotubes (GaNNTs). The vibrational characteristics of single-layered boron nitride nanosheet (BNNS)/single-walled BNNT (SWBNNT) junctions were studied by Rouhi et al [39].…”
Section: Introductionmentioning
confidence: 99%